2022
DOI: 10.3390/jcm11092487
|View full text |Cite
|
Sign up to set email alerts
|

General Purpose Pharmacokinetic-Pharmacodynamic Models for Target-Controlled Infusion of Anaesthetic Drugs: A Narrative Review

Abstract: Target controlled infusion (TCI) is a clinically-available and widely-used computer-controlled method of drug administration, adjusting the drug titration towards user selected plasma- or effect-site concentrations, calculated according to pharmacokinetic-pharmacodynamic (PKPD) models. Although this technology is clinically available for several anaesthetic drugs, the contemporary commercialised PKPD models suffer from multiple limitations. First, PKPD models for anaesthetic drugs are developed using deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…21,22 Continuous intravenous administration of Remifentanil can be performed using conventional infusion pumps and rate-of-use techniques that allow the anesthesiologist to select and adjust a target plasma concentration to achieve the desired pharmacodynamic effect. 23 The advantages of remifentanil over other opiates are great analgesic potency, short latency, rapid dosage, and elimination. For these reasons, it is the drug indicated in neurosurgical surgery since it provides hemodynamic stability, faster awakening, and better postoperative recovery than other opioids, allowing an immediate postoperative neurological evaluation.…”
Section: Neuroanesthesiamentioning
confidence: 99%
“…21,22 Continuous intravenous administration of Remifentanil can be performed using conventional infusion pumps and rate-of-use techniques that allow the anesthesiologist to select and adjust a target plasma concentration to achieve the desired pharmacodynamic effect. 23 The advantages of remifentanil over other opiates are great analgesic potency, short latency, rapid dosage, and elimination. For these reasons, it is the drug indicated in neurosurgical surgery since it provides hemodynamic stability, faster awakening, and better postoperative recovery than other opioids, allowing an immediate postoperative neurological evaluation.…”
Section: Neuroanesthesiamentioning
confidence: 99%
“…Table 1 shows some of the commercially available models with their boundaries [3][4][5][6][7][8][9][10]27]. A detailed comparison between the models was recently described by Vandemoortele et al [28]. They concluded that general-purpose models have the potential to increase the clinical acceptance of TCI, as there are less restrictions in their use compared with other models.…”
Section: Propofolmentioning
confidence: 99%
“…Using allometric scaling and maturation function on the PK parameters is a useful way of comparing model parameter estimates across studies 50,51 . These techniques have been discussed in a number of recent PKPD modeling reviews 21,52,53 …”
Section: Main Articlementioning
confidence: 99%
“… 50 , 51 These techniques have been discussed in a number of recent PKPD modeling reviews. 21 , 52 , 53 …”
Section: Main Articlementioning
confidence: 99%